Analysis of debris flow control effect and hazard assessment in Xinqiao Gully, Wenchuan Ms 8.0 earthquake area based on numerical simulation - Chang Yang; Yong-bo Tie; Xian-zheng Zhang; Yan-feng Zhang; Zhi-jie Ning; Zong-liang Li (China Geology)
ABSTRACT: Xinqiao Gully is located in the area of the 2008 Wenchuan Ms 8.0 earthquake in Sichuan province, China. Based on the investigation of the 2023 “6-26” Xinqiao Gully debris flow event, this study assessed the effectiveness of the debris flow control project and evaluated the debris flow hazards. Through field investigation and numerical simulation methods, the indicators of flow intensity reduction rate and storage capacity fullness were proposed to quantify the effectiveness of the engineering measures in the debris flow event. The simulation results show that the debris flow control project reduced the flow intensity by 41.05% to 64.61%. The storage capacity of the dam decreases gradually from upstream to the mouth of the gully, thus effectively intercepting and controlling the debris flow. By evaluating the debris flow of different recurrence intervals, further measures are recommended for managing debris flow events.